2019
DOI: 10.22323/2.18040204
|View full text |Cite
|
Sign up to set email alerts
|

Developing science tabletop games: ‘Catan’® and global warming

Abstract: ‘Catan’ ® (1995) is a multiplayer tabletop game with global sales of over 20 million copies. Presented here is an exploration of the steps that were taken in the development of the ‘Catan: Global Warming’ expansion, from prototype to final design. During the playtesting of the game the feedback that we received from a variety of playtesters indicated that the game mechanics (rather than any accompanying story) were an effective and elegant way of developing dialogue around a specific topic, in this instance gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Basically, board games can promote higher-order thinking skills (Kuo & Hsu, 2020). Science board games have been shown to help students understand computational thinking (Wangenheim et al, 2019) and complex environmental issues (Fjaellingsdal & Klöckner, 2020) such as global warming (Illingworth & Wake, 2019). In fact, science board games have been shown to help students understand complex concepts better than similar digital games.…”
Section: Engaged Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, board games can promote higher-order thinking skills (Kuo & Hsu, 2020). Science board games have been shown to help students understand computational thinking (Wangenheim et al, 2019) and complex environmental issues (Fjaellingsdal & Klöckner, 2020) such as global warming (Illingworth & Wake, 2019). In fact, science board games have been shown to help students understand complex concepts better than similar digital games.…”
Section: Engaged Learningmentioning
confidence: 99%
“…In comparison to digital games, science board games offer an ease of communication (Erb, 2015). In CATAN: GLOBAL WARMING, researchers found that the board game fostered scientific dialogue among the players (Illingworth & Wake, 2019). When compared to digital games, board games can afford more intensive communication patterns among players (Erb, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Ampatzidou and Gugerell (2019), we used different types of testers for distinctive purposes in order to get the most out of the participatory design process (see Lanezki, Siemer, and Wehkamp 2020). Environmental scientists and other topic experts were used to peer review the presented scientific content throughout the design process (Illingworth and Wake 2019). Testing with our main target audience—the Finnish stakeholders in land use planners, conservation, and development—allowed us to reflect how they received our framings of the topic and to get an early user feedback on the game design (see Mildner and Mueller 2016).…”
Section: Intervention—kompensaatiopeli Offsetting Gamementioning
confidence: 99%
“…For example, when we designed a “Global Warming” scenario [ 29 ] ( Fig 3 ) for the popular game Catan [ 30 , 31 ], we aimed to create an experience for our audience (regular gamers) that enabled them to revisit a familiar game but which invited them to reconsider the game’s themes of “settlement” (national expansion and resourcing) in the context of runaway global warming effects. In doing so, we were also inspired by the work of others who had successfully adapted Catan to engage gamers on topics ranging from sustainability [ 32 ] to colonialism [ 33 ].…”
Section: Introductionmentioning
confidence: 99%